Cooperation Between Health Programmers and Health Professionals : A CDD Experience - Sutoto Sutoto; Indriyono Indriyono (Paediatrica Indonesiana, 1990)
Just like many other health programmes, the success of the Control of Diarrhoeal Diseases (CDD) programme has to rely on the cooperation and coordination with other health programmes or non-health programmes. This cooperation is usually referred to as a cross programme or a cross sectoral activities. The COD programme in Indonesia is managed by the Subdirectorate of Diarrhoea under the Directorate General for Communicable Disease Control and Environmental Health. According to the Decree of the Minister of Health No. 558 of 1984 the Subdirectorate of Diarrhea is designed to plan, implement and evaluate COD programme. Diarrhoea is still considered to be a major public health problem due to its high mortality and morbidity.